Linguistic Difficulties In Translating English to Indonesian and Indonesian to English of EFL Students - Syahril Mubarok (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study aims to investigate the linguistic factors of university students’ difficulties in translating sentences from English to Indonesia and vice versa. There are five linguistic factors investigated in this research, those are lexical, dictionary entries, syntactic, ellipsis, and idiom. Therefore, the research problem was consisted of which type of translation was more difficult and which linguistic factor was the most difficult for university students at the University of Islam Malang (UNISMA). Hence, the researcher used a descriptive qualitative design on students of the fifth semester at A class which consisted of 36 students. 10 students were chosen based on the lowest score in the translation subject and were administered to the translation test consisting of 9 numbers to translate from English to Indonesia and 6 numbers to translate from Indonesian to English. 5 students who got the lowest score on the test were interviewed to get deep information about their difficulties with those five linguistic factors. The result showed by the least percentage means the most difficult factor, it is indicated that the most difficult linguistic factors is related to idiom and followed by ellipsis with and dictionary entries with, then syntactic factors and lastly lexical problem. Moreover, this study also found that when translating sentence from Indonesian to English, the most difficult is dictionary entries, which followed by ellipsis and then syntactic as well as lexical. The result of the study suggested for the university students to learn more about the linguistic components, especially in translating sentences both from Indonesian to English and vice versa.Key Words: linguistic factors, sentence, and translation